The Urban Development Investment Corporations (UDICs) in Chongqing, China - World Bank (World Bank, 2012)
Urban Development Investment Corporations (UDICs) have over the years become the central pillar in the local government drive to build infrastructure in China, where local governments are not allowed to engage in direct market borrowing. UDICs were established during the early 1990s when local governments were under great pressure to both build municipal infrastructure and to reform the role of the government in infrastructure development. The UDIC model provided the local governments with a corporate government structure to borrow from the market and quickly develop infrastructure. They are treated as municipal corporations under the Company Law of the Peoples' Republic of China (PRC). The law does not clarify the relationship between UDICs and the local government, including the limits of the financial liability of the local governments vis-a-vis UDICs. The Government of China (GOC) agencies expect that the World Bank (WB) Technical Assistance Report (TAR), based on the detailed analysis of the financial operations of a selected UDIC in Chongqing, will offer critical technical assistance to the Chongqing Municipal Government (CMG), which can also be shared with other Chinese cities. The GOC agencies realize that this TAR is the first step in the right direction, in that it will specifically address the needs of a reform-minded municipal government and clarify one UDIC model in detail. It is anticipated that similar efforts can be undertaken in the coming years with other reform-minded and high-priority cities that are employing different models of UDIC to finance municipal infrastructure.